A bridge too far: the dilemma of transport development in peripheral mountain areas - Michal Apollo (Journal of Tourism Futures)
Purpose – Transportation infrastructure and destination accessibility are essential in developing the tourism industry. However, the situation is somewhat different in mountain peripheral areas, where poor accessibility is a kind of tourist attraction but also a driver of regional development. Thus, improving accessibility by “a bridge too far” can mean not just a lack of development but its regression and even the end of mountain tourism as we know it. Design/methodology/approach – This exploratory ethnographic study aims to understand accessibility improvement and its impact on local communities. The data were collected in the Nepalese Khumbu region, which is the home of the Everest Base Camp Trek. Based on 18 in-depth interviews, this paper tested a proposed model of the evolution of a peripheral mountain area under the influence of transport development. Findings – This study demonstrates the threats to local communities from the transport development (road and air) and improved tourist accessibility of a peripheral area that profits from its peripherality. Research shows unequivocally that transport development may result in the loss of business for many of them. Overall, in the opinion of the local communities, unplanned road and air transport development is destroying mountain tourism in this area. Originality/value – To date, research on accessibility development in mountainous areas shows the main positive sides of change. This article contributes to understanding how accessibility improvements change people’s lives and how these changes can become “community killer”.